2005
DOI: 10.2174/138527205774610895
|View full text |Cite
|
Sign up to set email alerts
|

Cycloadditions, Cycloisomerizations and Related Reactions of Alkynes Bearing Group 13 or 14 Heteroelements

Abstract: Cycloaddition and cycloisomerization reactions involving alkynes grant a rapid access to arenes, cyclic dienes, and cyclopentenone derivatives. The use of alkynes substituted by group 13 or 14 heteroelements as partners for such reactions is an emerging strategy. Indeed, the specific electronic properties of these heteroelements can play a crucial role for controlling the chemo-and regioselective outcome of a given reaction. Moreover, the heteroatoms can be considered as latent functional groups and would allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Introduction of main group heteroelements to unsaturated partners such as olefins, acetylenes, allenes and 1,3-dienes may have a dramatic influence on the product distribution of the cycloadditions. 24 For instance, they can control the chemoand regioselectivities. Besides, they can confer kinetic stabilization and allow the preparation of structural moieties which would be hardly accessible in the unsubstituted series.…”
Section: Alkynyl Boronic Esters: Synthesis Of Fused Arylboronic Ester...mentioning
confidence: 99%
“…Introduction of main group heteroelements to unsaturated partners such as olefins, acetylenes, allenes and 1,3-dienes may have a dramatic influence on the product distribution of the cycloadditions. 24 For instance, they can control the chemoand regioselectivities. Besides, they can confer kinetic stabilization and allow the preparation of structural moieties which would be hardly accessible in the unsubstituted series.…”
Section: Alkynyl Boronic Esters: Synthesis Of Fused Arylboronic Ester...mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Moreover, the cycloaddition products can be used in subsequent reactions to obtain complex structures. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Moreover, the cycloaddition products can be used in subsequent reactions to obtain complex structures.…”
Section: Introductionmentioning
confidence: 99%
“…Alkynyl boron reagents have shown great versatility as building blocks in several cycloaddition reactions leading to a wide variety of compounds in a regioselective manner. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Moreover, the cycloaddition products can be used in subsequent reactions to obtain complex structures. Among these compounds, alkynylboranes have proved to be good dienophiles showing an unusual electronic preference for the meta products in Diels-Alder (DA) reactions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our research group demonstrated that cationic rhodium(I)/biaryl bisphosphine complexes are highly effective catalysts for the [2 + 2 + 2] cycloaddition to produce substituted arenes under mild reaction conditions. Furthermore our research group demonstrated that the rhodium-catalyzed double [2 + 2 + 2] cycloaddition is an effective method for the synthesis of symmetric biaryls, spiranes, and helicene-like molecules . We anticipated that the rhodium-catalyzed double [2 + 2 + 2] cycloaddition between dialkynyl phosphine oxides , and tetraynes would be useful for the synthesis of symmetric and regioselectively substituted phosphafluorenes because of the facile preparation of dialkynyl phosphine oxides from the corresponding terminal alkynes and dichlorophosphine oxides (Scheme ).…”
mentioning
confidence: 99%